2021
DOI: 10.1002/ar.24648
|View full text |Cite
|
Sign up to set email alerts
|

The sesamoid bone in the long abductor muscle tendon of the first digit in the dog

Abstract: The sesamoid bone in the tendon of the m. abductor digiti primi longus is considered present in most dog breeds and is described to be radiologically detectable at the level of the carpus from the age of 4 months. However, an extensive investigation of this sesamoid bone has not been conducted before. The aim of this study was therefore to determine its prevalence in different dog breeds, to describe its histological development, and to determine the age at which it becomes radiologically visible. The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 77 publications
1
7
0
Order By: Relevance
“…The clinical differences between the sexes were small (maximum of 5 days' difference in median age), but there was a tendency for an earlier onset of ossification in female puppies. Most previous studies on the occurrence of OCs or growth plate closure in dogs did not distinguish between female and male dogs 15,24,30,34,36,37,39,41,46,48 ; our results are consistent with the few studies that did make a distinction. 25,28,49,50 In human research, it is generally reported that OCs appear significantly earlier in females than in males, with the consequence that standardised methods to evaluate skeletal development have to be gender differentiated.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The clinical differences between the sexes were small (maximum of 5 days' difference in median age), but there was a tendency for an earlier onset of ossification in female puppies. Most previous studies on the occurrence of OCs or growth plate closure in dogs did not distinguish between female and male dogs 15,24,30,34,36,37,39,41,46,48 ; our results are consistent with the few studies that did make a distinction. 25,28,49,50 In human research, it is generally reported that OCs appear significantly earlier in females than in males, with the consequence that standardised methods to evaluate skeletal development have to be gender differentiated.…”
Section: Discussionsupporting
confidence: 91%
“…45 The majority of the dorsopalmar radiographs (215 carpi of 109 dog cadavers and 140 carpi of 100 dogs in the retrospective study) were previously studied to evaluate the absence or presence of the sesamoid bone. 46 Adding additional radiographs did not change the conclusions of this study regarding the timeline of ossification of the carpal sesamoid bone, namely, that a sesamoid bone is visible on radiographs in the majority of puppies from 121 days onwards. Presence in 100% of the dogs studied may not be achieved as the carpal sesamoid bone may be radiologically absent in some breeds, such as the French Bulldog and Chow Chow.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations